Crushing the Tradition: Does Cyberloafing Provide Potential Learning? - Mayasari, Desy (Jurnal Nasional Manajemen Pemasaran dan SDM, 2025)
This study bridges the domains of creativity and deviance by exploring the nuanced relationship between creative self-efficacy, creative deviance, and cyberloafing behaviors—specifically emailing and web surfing activities. Recognizing cyberloafing not merely as counterproductive behavior but as a potential catalyst for creative performance. Therefore, this research investigates its dual role as both an outlet for creative expression and a learning mechanism within organizational settings. The findings reveal that individuals with higher creative self-efficacy and a propensity for creative deviance are more inclined to engage in cyberloafing. Moreover, the data demonstrates that certain cyberloafing activities, particularly emailing, positively influence creative performance outcomes. These results challenge traditional perceptions of workplace deviance and underscore the importance of re-evaluating informal digital behaviors as contributors to innovation. Theoretical implications for creativity research and practical recommendations for managing creative work environments are discussed in depth.